Performing Technology : User Content and the New Digital Media. - Schroeder, Franziska (Cambridge Scholars Pub., 2009)
This volume emerged out of the discussions during the 2009 edition of the Two Thousand + symposia series at the Sonic Arts Research Centre, Belfast. In 2009 the symposium focused on user-generated content and it is the refined and reworked writings that have been included in this volume. The texts in this book cover the development of design strategies for addressing rich media environments that incorporate user-generated, locative content. Chapters cover areas such as choreography/dance, vir ...